Sequential Gaussian Simulation of uranium spatial distribution : a transboundary watershed case study - Albuquerque, M.T.D. (2015)
Este artigo deriva de uma comunicação apresentada em International workshop “Uranium, Environment and Public Health”, UrEnv 2013.